The first report from Poland and larvae description of Eukiefferiella dittmari Lehmann, 1972 (Diptera: Chironomidae) based on morphological and molecular characteristics - Słomczyński, Kamil; Matera, Tymoteusz; Brodecki, Jarosław; Gadawski, Piotr; Płóciennik, Mateusz (Zootaxa, 2025)
Eukiefferiella is a large genus in the family Chironomidae with over 50 species worldwide. Their immature stages have so far been described in many species in the western Palearctic. Nevertheless, some species are still known only from adult males. Presented below is a description of Eukiefferiella dittmari Lehmann, 1972 larvae first recorded in Poland in the pristine river Rawka. The larvae were collected from water moss and identified to the species level using a DNA barcode from BOLD database. E. dittmari larvae belong to E. ilkleyensis group having bifid SIII seta, and mentum with wide central tooth and four pairs of lateral teeth. At the genetic and morphological level, E. dittmari is a sister species to Nearctic E. endobryonia, also an aquatic moss dweller. The phylogenetic relation of these two species should be further investigated.